2018
DOI: 10.1007/s00520-018-4398-4
|View full text |Cite
|
Sign up to set email alerts
|

“…It might not have occurred to my husband that this woman, his wife who is taking care of him has some emotional needs as well…”: the unheard voices of partners of Black African and Black Caribbean men with prostate cancer

Abstract: Cultural beliefs, behaviours and values should be taken into account when developing psychosocial support for partners and their men with CaP. Specifically providing information focused on partners and including them in the CaP care pathway could help ensure that partners' needs are recognised and improve marital communications. This could potentially help partners and their men to identify acceptable ways of supporting each other throughout the CaP experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(64 citation statements)
references
References 18 publications
1
62
1
Order By: Relevance
“…The women mostly coped by prioritising their caregiving roles over own psychological and emotional needs, using distractions (eg, work and childcare), feeling sympathetic and loyal towards their husbands, and also by praying. A detailed discussion of partners’ experiences has been reported elsewhere …”
Section: Resultsmentioning
confidence: 99%
“…The women mostly coped by prioritising their caregiving roles over own psychological and emotional needs, using distractions (eg, work and childcare), feeling sympathetic and loyal towards their husbands, and also by praying. A detailed discussion of partners’ experiences has been reported elsewhere …”
Section: Resultsmentioning
confidence: 99%
“…Sexual issues, including masculinity, also seemed to be a barrier to communication within African American couples facing PCa (Friedman et al, 2012). The role of masculinity and sexuality is pervasive in the PCa literature and is echoed in literature on African American couples when considering treatment decisions, sexual aids, and other concerns (Bamidele, Lagan, et al, 2019). Given that the experience of having PCa, from diagnosis to survivorship, has psychosocial effects unique to African American survivors and their partners, it is important to examine some of the counseling concerns that are specific for African American couples facing the disease (Rivers et al, 2012).…”
Section: What Counselors Should Know About Pcamentioning
confidence: 99%
“…Furthermore, the concerns of partners may differ from the concerns of survivors, who worry more about mortality than the side effects of the disease or treatment (Rivers et al, 2011). Bamidele, Lagan, et al (2019) found that partners experience isolation and sometimes feel as though they are a “co‐patient” (p. 1092). Although much of this information is provided by medical professionals, one of the main sources of information for Africa American PCa survivors are their partners (Walsh‐Childers et al, 2018).…”
Section: Pca Concerns For Couplesmentioning
confidence: 99%
See 2 more Smart Citations